2012
DOI: 10.1002/biot.201200174
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale structure of type I collagen fibrils: Quantitative measurement of D‐spacing

Abstract: This paper details a quantitative method to measure the D-periodic spacing of Type I collagen fibrils using Atomic Force Microscopy coupled with analysis using a 2D Fast Fourier Transform approach. Instrument calibration, data sampling and data analysis are all discussed and comparisons of the data to the complementary methods of electron microscopy and X-ray scattering are made. Examples of the application of this new approach to the analysis of Type I collagen morphology in disease models of estrogen depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 47 publications
(84 reference statements)
3
52
1
Order By: Relevance
“…6,7 Recent AFM studies indicated changes in the nanomorphology of the Type I collagen fibrils in ovariectomized (OVX) sheep [8][9][10] and rats. 11 In order to explore the effect of estrogen depletion and compare efficacy of CatKI and alendronate (ALN) drug treatments, the rabbit OVX model was developed by Merck Inc., as human CatKI's exhibit similar potency for the rabbit enzyme and the adult rabbit skeleton undergoes substantial cortical Haversian remodeling (unlike the rodent).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Recent AFM studies indicated changes in the nanomorphology of the Type I collagen fibrils in ovariectomized (OVX) sheep [8][9][10] and rats. 11 In order to explore the effect of estrogen depletion and compare efficacy of CatKI and alendronate (ALN) drug treatments, the rabbit OVX model was developed by Merck Inc., as human CatKI's exhibit similar potency for the rabbit enzyme and the adult rabbit skeleton undergoes substantial cortical Haversian remodeling (unlike the rodent).…”
Section: Resultsmentioning
confidence: 99%
“…Details on sample preparation, imaging and image analysis protocols for Type I collagen in bone have been previously published. 6 Images were obtained from locations from across the full 1.00 Â 0.75 cm section of the femur mid-diaphysis (Supplementary Figure S1). All images were acquired in the plane parallel to the long bone axis and obtained from polished regions 100-300 mm below the bone surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, regarding imaging techniques, AFM and electron microscopy techniques can directly image mineralized collagen fibrils, with a FOV covering areas at a scale of tens of nanometres to a few tens of micrometres [9]. Imaging bone at this scale provides useful information on other structural features, such as the collagen -mineral interface [21], mineral platelet sizes and shapes [13,14] or collagen D-period [7,263] for very high-resolution techniques such as TEM and AFM, and offers data revealing structural details of the lacuno-canalicular network [245] and bone remodelling sites [270] for high-resolution techniques such as SEM. X-ray phase-contrast techniques such as ptychographic CT [225] or X-ray phase nanotomography [226] operate at similar scales to volume SEM, and in addition offer the important advantage of tomographic (i.e.…”
Section: Assessment At Different Hierarchical Levels and Additional Imentioning
confidence: 99%
“…At each location, 10-15 fibrils were analyzed in error images (B70 fibrils per bone) using two-dimensional fast Fourier transforms (2D FFTs) as described previously. [36][37][38][39] Briefly, 2D FFTs were performed on an area of interest over individual fibrils so that the first harmonic peak from the power spectrum represented the D-spacing for that fibril.…”
Section: Atomic Force Microscopymentioning
confidence: 99%